The Carrot and the Stick: The Business Cycle Implications of Incentive Pay in the Labor Search Model - Julien Champagne (Bank of Canada, 2015)
This paper considers a real business cycle model with labor search frictions where two types of incentive pay are explicitly introduced following the insights from the micro literature on performance pay (e.g. Lazear, 1986). While in both schemes workers and firms negotiate ahead of time-t information, the object of the negotiation is different. The first scheme is called an "efficiency wage," since it follows closely the intuition of the shirking model by Shapiro and Stiglitz (1984), while the second is called a "performancepay" wage, since the negotiation occurs over a wage schedule that links the worker's wage to the worker's output. The key feature here is that the worker can then adjust the level of effort (i.e. performance) provided in any period. I simulate a shift toward performance-pay contracts as experienced by the U.S. labor market to assess whether it can account simultaneously for two documented business cycle phenomena: the increase in relative wage volatility and the Great Moderation. While the model yields higher wage volatility when performance pay is more pervasive in the economy, it produces higher volatility of output and higher procyclicality of wages, two results counterfactual to what the U.S. economy has experienced during the Great Moderation. These results pose a challenge to the idea that higher wage flexibility through an increase in performance-pay schemes can account for business cycle statistics observed over the past 30 years.
Keywords: E24; J33; J41; 330; Business fluctuations and cycles; Labour markets